Teams-Games-Tournament (TGT) to Teach Vocabulary of English for Specific Purpose in Increasing Students’ Self-Esteem - Sunarti Sunarti; Rani Herning Puspita; Abdul Halim (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2019)
The objective of this study was to investigate the implementation of playing game on students’ mastery on vocabulary of ESP viewed from self-esteem in producing words. The investigation were: (1) to know whether Teams-Games-Tournament (TGT) was more effective than Grammar Translation Method (GTM) to teach vocabulary of ESP; (2) to know whether the students whose self-esteem was high had better vocabulary of ESP mastery than those who had low self-esteem; and (3) to prove whether there was an interaction between teaching methods and self-esteem to teach vocabulary of ESP.